FORMULASI HUKUM DAN PENTINGNYA JAMINAN KEPASTIAN HUKUM PRODUK PANGAN HALAL DALAM HUKUM NASIONAL - Sofyan, KN (Nurani, 2015)
Abstract: The Food Act No.18 of 2012 is in the government'sdevelopment efforts of food to meet the basic needs of theIndonesian people in a fair and equitable based onindependence and not contrary to the religion, beliefs and,cultur of society. Related to food safety hazards includingdangerous category of "unlawful and or dubious" its effect doesnot seem as effects of chemical contamination, physical andmicrobiological direct implications for health problems. Theimportance of the legal aspects of drug and food labeling,related with the ever-increasing consumer demands, especiallyregarding the halal aspect. This issue has been legallyregulated by government, both in the food laws, consumerprotection laws and regulations governing government is moretechnical. With the certification of halal food products becamepublic consumption, is one of the government's efforts to protectconsumers against 88% Muslim community.ملخص: قانون الأغذیة 18 لسنة 2012 في جھود التنمیة في الحكومة من الموادالغذائیة ل تلبیة الاحتیاجات الأساسیة للشعب الإندونیسي في الثقافیھ عادلة ومنصفةعلى أساس الاستقلال و الذي لا یتعارض مع الدین، والمعتقدات، و المجتمع . تتعلقمخاطر سلامة الأغذیة بما في ذلك فئة خطیرة من "غیر قانوني و أو مشكوك فیھا" لایبدو أثره كما آثار التلوث الكیمیائي، والآثار المباشرة الفیزیائیة و المیكروبیولوجیةللمشاكل الصحیة. أھمیة الجوانب القانونیة لوضع العلامات المخدرات والمواد الغذائیة،ذات الصلة مع طلبات المستھلكین المتزایدة، وخاصة فیما یتعلق بالجانب الحلال. وقدتم تنظیم ھذه المسألة من الناحیة القانونیة من قبل الحكومة، سواء في قوانین الطعاموالقوانین واللوائح التي تنظم حمایة المستھلك الحكومة ھو أكثر تقنیة. مع إصدارالشھادات للمنتجات الأغذیة الحلال أصبحت الاستھلاك العام، ھي واحدة من الجھودالتي تبذلھا الحكومة لحمایة المستھلكین ضد المجتمع المسلم.Kata Kunci : halal, hukum produk pangan